EL COMERCIO DE CUADROS ESPAÑA-ITALIA A TRAVÉS DEL LEVANTE ESPAÑOL A COMIENZOS DEL SIGLO XVII - Agüera Ros, José Carlos (Imafronte, 1991)
Among the artistic contacts beween Spain and Italy. the importation of paintings from this latter country hada special importance for the renewal and development of our painting during the Golden Age. A great number of consignments of Italian works, the final destination of which were Madrid, arrived in several port cities at the Spanish Mediterranean coast, mainly Valencia. Those were frequently brought by the Italian painters themselves, like the Tuscan Salustio Lucchi. Agent of the trade company established by his uncle Pietro Sorri of Sienna at the beginning of the 17th century, Lucchi and other colleagues of him became un outstanding example of the above mentioned phenomenon.